Co-delivery of metformin and levofloxacin hydrochloride using biodegradable thermosensitive hydrogel for the treatment of corneal neovascularization - Liu, Dong (Drug Deliv, 2019)
Corneal neovascularization (CNV) is one of the major causes of severe disorders in ocular surface. Subconjunctival administration provides a localized and effective delivery of anti-angiogenic agents to inhibit neovascularization. In the present study, the ABA triblock copolymer of poly(D,L-lactic-co-glycolic acid)-block-poly(ethylene glycol)-block-poly(D,L-lactic-co-glycolic acid) (PLGA-PEG-PLGA) was used as a sustained drug delivery carrier for metformin (MET) and levofloxacin hydrochloride (LFH). Both drugs and PLGA-PEG-PLGA copolymers could be easily dissolved in water at low or room temperature and the mixed solution could form a drug-loaded thermosensitive hydrogel in terms of body temperature response. The in vitro release investigation displayed a sustained release of MET and LFH from the formulation for one month. The in vivo efficacy of subconjunctival injection of the MET + LFH loaded thermosensitive hydrogel in inhibiting CNV was evaluated on a mouse model of corneal alkali burn. Compared with the single administration of MET or LFH loaded thermosensitive hydrogel, the MET + LFH loaded thermosensitive hydrogel remarkably inhibited the formation of CNV. The sustained release of MET and an antibiotic (LFH) provides synergistic therapeutic outcome. As a result, the co-delivery of MET and LFH using PLGA-PEG-PLGA thermosensitive hydrogel by subconjunctival injection has great potential for ocular anti-angiogenic therapy.